Pembelajaran Musik Rejung Menggunakan Media Audio Visual (Video Tutorial) - Siswanto, Silo Siswanto; Haque, Zelly Marissa (UNIVERSITAS INDO GLOBAL MANDIRI)
The Learning of local music in schools and universities had become the pre-eminent material as local content in every place in Indonesia, in this case, the focus of discussion on this paper was Rejung music or often called as Batang Hari Sembilan, the identification of problems in this research was in the learning process of Rejung music, where the music educators had difficulties in teaching this material because the steps of rejung music learning material were not well compiled. In addition, the problems faced by educators in learning Rejung music was the learning media was not utilized optimally, namely, audio-visual media (learning tutorial video). Based on the identification of the problem, The problem in this research could be formulated in the form of questions as follows, 1) How was the structure of Rejung music. 2) how to make /produce tutorial video in Rejung Music learning. 3) How to learn Rejung music through tutorials video. While the specific objectives of this study were 1) Explained the music playing technique in Rejung music. 2) Explained the video tutorial production. 3) Explained the learning process of Rejung music through tutorial video. The method used in this research was this research discussed matters related to the science of Rejung music, the data collection was done through observation and documentation related to the learning process of the local music. Furthermore, the analysis of data related to Rejung music was processed and formulated through musicology and audio-visual multimedia.